Chorizopesoides, a new genus of orb-weaver spider from China (Araneae: Araneidae). (2nd January 2018) - Mi, Xiaoqi; Wang, Cheng
Abstract: A new genus, Chorizopesoides, is erected for two known araneid species ( C. wulingensis (Yin, Wang & Xie, 1994)comb. n., the type species from China and C. orientalis (Simon, 1909)comb. n. from Vietnam and China), both transferred from Chorizopes O. Pickard-Cambridge, 1871. Chorizopesoides wulingensis and C. orientalis are re-described, and the males of the two species are described for the first time. The differences between the new genus and Chorizopes are also discussed. Distributional data and illustrations of somatic and genital morphology are provided. http://zoobank.org/urn:lsid:zoobank.org:pub:0ED3D6FB-6110-4493-87DD-DCA858AEEEAF